Glucose concentration during equine in vitro maturation alters mitochondrial function. Issue 2 (August 2020) - Lewis, Niamh; Hinrichs, Katrin; Leese, Henry J; McGregor Argo, Caroline; Brison, Daniel R; Sturmey, Roger G
Abstract : The use of in vitro embryo production in the horse is increasing in clinical and research settings; however, protocols are yet to be optimised. Notably, the two most commonly used base media for in vitro maturation ( IVM ) supply glucose at markedly different concentrations: physiological (5.6 mM, M199) or supraphysiological (17 mM, DMEM/F-12). Exposure to high glucose has detrimental effects on oocytes and early embryos in many mammalian species, but the impact has not yet been examined in the horse. To address this, we compared the energy metabolism of equine COCs matured in M199-based maturation medium containing either 5.6 or 17 mM glucose, as well as expression of key genes in oocytes and cumulus cells. Oocytes were fertilised by ICSI and cultured. Analysis of spent medium revealed that COC glucose consumption and production of lactate and pyruvate were similar between treatments. However, the glycolytic index was decreased at 17 mM and analysis of mitochondrial function of COCs revealed that IVM in 17 mM glucose was associated with decreased ATP-coupled respiration and increased non-mitochondrial respiration compared to that for 5.6 mM glucose. We also found that the metabolic enzyme lactate dehydrogenase-A ( LDHA ) was downregulated in cumulus cells of oocytes that completed IVM in 17 mM glucose. There was no difference in maturation or blastocyst rates. These data indicate that COC mitochondrial function and gene expression are altered by high glucose concentration during IVM. Further work is needed to determine if these changes are associated with developmental changes in the resulting offspring.